Impacts and benefits of the implementation of the Civil Service Law in the UNMSM - Moriano Sauñe, Nancy Yesenia (2021)
The objective of this research was to determine if the implementation of the Civil Service Law influences the improvement of the institutional management of the Universidad Nacional Mayor de San Marcos (UNMSM) in order to demonstrate and sensitize the authorities based on experiences national and international successes, the impacts and benefits it represents for the University, being within a transition process towards the new Civil Service regime established by the National Civil Service Authority (SERVIR); This research is of an applied type of descriptive level and its design is non-experimental, since it does not imply the change of the variables. With a stratified sample with a Cronbach’s Alpha result of 85%. Concluding that the implementation of this service positively influences the improvement of Institutional Management in the UNMSM that allows the introduction of meritocracy by establishing a system of revaluation and professionalization of the Public Servant. We conclude that the implementation of the Civil Service has a positive influence on the improvement of Institutional Management in the UNMSM that allows the introduction of meritocracy by establishing a system of revaluation and professionalization of the Public Servant.